Search for direct CP violation in D0 -> h- h+ modes using semileptonic B decays - collaboration, L; Aaij, R; Beteta, C; Adeva, B; Adinolfi, M; Adrover, C; Affolder, A; Ajaltouni, Z; Albrecht, J; Alessio, F; Alexander, M; Ali, S; et al. (2013)
A search for direct CP violation in D0 -> h- h+ (where h=K or pi) is presented using data corresponding to an integrated luminosity of 1.0 fb^-1 collected in 2011 by LHCb in pp collisions at a centre-of-mass energy of 7 TeV. The analysis uses D0 mesons produced in inclusive semileptonic b-hadron decays to the D0 mu X final state, where the charge of the accompanying muon is used to tag the flavour of the D0 meson. The difference in the CP-violating asymmetries between the two decay channels is measured to be Delta A_CP = A_CP(K-K+) - A_CP(pi-pi+) = (0.49 +- 0.30 (stat) +- 0.14 (syst)) % . This result does not confirm the evidence for direct CP violation in the charm sector reported in other analyses.